Rapid and conformal coating of polymer resins by airbrushing for continuous and high-speed roll-to-roll nanopatterning: parametric quality controls and extended applications - Jae Hyuk Lee (Nano Convergence, 2017)
Abstract We present a facile and scalable coating method based on controlled airbrushing, which is suitable for conformal resin coating in continuous roll-to-roll (R2R) nanoimprint lithography (NIL) process. By controlling the concentration of UV-curable polymeric resin with mixing the volatile solvent and its airbrushing time, the coated resin film thickness can be readily tuned. After R2R NIL using a flexible nanoscale line pattern (nanograting) mold is conducted upon the airbrushed resin film, a large-area uniform nanograting pattern is fabricated with controlled residual layer thickness (RLT) based on the initial film thickness. We investigate the faithful airbrushing condition that can reliably create the uniform thin films as well as various nanopatterns with controlled morphologies. Using more diluted resin and shorter airbrushing time can reduce the RLTs favourably for many applications, yet is apt to induce the nanoscale pores and discontinued lines. We also discuss how to further improve the quality and scalability of resin airbrushing and its potential applications particularly requiring high-speed and conformal coating on highly topographic and flexible surfaces.